2011
DOI: 10.1249/01.mss.0000402484.45084.5e
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Antioxidants Are Increased In Adolescents With Down Syndrome After A 12-week Training Program

Abstract: It is generally accepted individuals with Down syndrome suffer from higher oxidative damage when compared to matched-healthy siblings. Fortunately we have recently found aerobic training at low/moderate intensity improved antioxidant defense system and reduced both lipoperoxidation and protein oxidation. To assess these parameters most studies use blood samples. Accordingly to our knowledge there is little information regarding its influence in non-invasive biomarkers of antioxidant system in Down syndrome. PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Individuals with ID often have health care concerns such as diabetes, kidney disease, severe allergies, progressive illnesses, respiratory weaknesses, and obesity. The National Survey of Children with Special Health Care Needs Survey (Centers for Disease Control and Prevention, 2005-2006, 2009 indicated individuals with disabilities with special health care needs often fail to learn how to manage their health issues and access needed health care services, which puts them at risk for failure in being able to hold a job, get a higher education degree, and live independently in the community. Rimmer et al (2010) found youths with autism and Down syndrome were 2 to 3 times more likely to be obese than adolescents in the general population.…”
Section: Health Needs and Intellectual Disabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with ID often have health care concerns such as diabetes, kidney disease, severe allergies, progressive illnesses, respiratory weaknesses, and obesity. The National Survey of Children with Special Health Care Needs Survey (Centers for Disease Control and Prevention, 2005-2006, 2009 indicated individuals with disabilities with special health care needs often fail to learn how to manage their health issues and access needed health care services, which puts them at risk for failure in being able to hold a job, get a higher education degree, and live independently in the community. Rimmer et al (2010) found youths with autism and Down syndrome were 2 to 3 times more likely to be obese than adolescents in the general population.…”
Section: Health Needs and Intellectual Disabilitiesmentioning
confidence: 99%
“…Low rates of physical activity put individuals at risk for obesity, heart disease, and type 2 diabetes (Centers for Disease Control and Prevention, 2021). Vigorous activity can be used to manage weight in people with Down syndrome (Ordonez et al, 2006) and lead to weight reduction. Regular physical activity can lead to healthier physical and psychosocial outcomes through body weight regulation (Garcia-Pastor et al, 2019).…”
Section: Health Needs and Intellectual Disabilitiesmentioning
confidence: 99%